2020
DOI: 10.48550/arxiv.2006.07047
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A relational perspective on the Wigner-Araki-Yanase theorem

Leon Loveridge

Abstract: We present a novel interpretation of the Wigner-Araki-Yanase (WAY) theorem based on a relational view of quantum mechanics. Several models are analysed in detail, backed up by general considerations, which serve to illustrate that the moral of the WAY theorem may be that in the presence of symmetry, a measuring apparatus must fulfil the dual purpose of both reflecting the statistical behaviour of the system under investigation, and acting as a physical reference system serving to define those quantities which … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…For example, Refs. [2,7,8,[33][34][35][36]49] use standard quantum information techniques to define external relatum independent states, but also use the latter to explore to some degree the question of how a quantum state is described relative to a subsystem. However, these works do not study the relations between the different such descriptions and thus, in particular, do not study the QRF transformations.…”
Section: A Describing Physics With or Without External Relatummentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Refs. [2,7,8,[33][34][35][36]49] use standard quantum information techniques to define external relatum independent states, but also use the latter to explore to some degree the question of how a quantum state is described relative to a subsystem. However, these works do not study the relations between the different such descriptions and thus, in particular, do not study the QRF transformations.…”
Section: A Describing Physics With or Without External Relatummentioning
confidence: 99%
“…But since all physical systems are fundamentally quantum, reference frames must ultimately be quantum systems, too. This simple insight is of fundamental importance in a variety of physical fields, including quantum information theory [1][2][3][4][5][6][7][8], quantum thermodynamics [9][10][11][12][13][14][15][16][17], quantum gravity [18][19][20][21][22][23][24][25][26], and in the foundations of quantum physics [27][28][29][30][31][32][33][34][35][36][37] more generally.…”
Section: Introductionmentioning
confidence: 99%
“…However, all physics is ultimately quantum, and thus it is crucial to realize that frames of reference are ultimately quantum systems, too. The consequences of this fundamental insight permeate several areas of physics, including quantum gravity [2][3][4][5][6][7][8][9], quantum thermodynamics [10][11][12][13][14][15][16][17][18], quantum information theory [19][20][21][22][23][24][25][26], and the foundations of quantum physics [27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…One natural example arises in the presence of conserved quantities. The Wigner-Araki-Yanase (WAY) theorem [4,5,6,7,8,9] shows that conservation laws restrict the accuracy and repeatability properties of a class of quantum measurements. Also in the presence of an additive conserved quantity, Åberg [10] has shown that any unitary dynamics can be approximately realized by preparing "coherent" (thus asymmetric) states of the environment.…”
Section: Introductionmentioning
confidence: 99%